Protected Data Using Hybrid Algorithm in Cloud - Kalaiselvi, K; Jayashri, N; Saraswathi, G (International Journal of Engineering and Technology, 2018)
Cloud computing providing confidentiality over the insensitive data was the major issue related to security. It verifies the data owned by the server through linear computations. The proposed work enables security and efficiency using the cryptographic techniques of hybrid algorithms, securing the sensitive information that is present in the cloud. In the hybrid algorithm, it is the combination of problem encryption, key generation, result decryption and proof generation. It also validates the results which are being computed and also provides end-to-end confidentiality over the data to both the end user. The uses of hybrid algorithm results in a random key generation, encrypt/decrypt, and validate the satisfied results. This will provide a low cost to both server and client.Â Â